STUDI PERBANDINGAN PROFIL ASAM LEMAK PADA IKAN SIDAT (Anguilla marmorata) DAN SIDAT (Anguilla bicolor) ASAL DANAU POSO KABUPATEN POSO PROVINSI SULAWESI TENGAH - Dewi Muhtiani; Nurlina Ibrahim; Jamaluddin Jamaluddin (Biology Department, Mathematics and natural science, Tadulako University, 2020)
Sidat fish (Anguilla marmorata) and Sidat fish (Anguilla bicolor) originate from Poso lake are endemic fish of Central Sulawesi but unknown its nutritional content. This study aims to determine the type, amount of composition and differences in the composition of fatty acids in Sidat fish (Anguilla marmorata) and Sidat fish (Anguilla bicolor). Testing fatty acid composition using Gas Chromatography method by converting fat extraction result into FAME (Fatty Acid Methyl Ester) form. The results showed that the amount of fatty acid content was not significant between the two samples. The fatty acid compositions found in Sidat (Anguilla marmorata) A, B and C fish include saturated fatty acids (2.62%), (2.81%), and (2.6%), monounsaturated fatty acids (1.98% ), (1.99%), and (10.1%), compound unsaturated fatty acids (0.635%), (0.812%), and (2.56%), mean while Sidat fish (Anguilla bicolor) A, B and C include saturated fatty acids (2.7%), (2.86%), and (12.704%), monounsaturated fatty acids (1.99%), (2.52%), (10.147%), and fatty acids unsaturated compounds (0.693%), (0.86%), and (2.615%).